Feeding and lipophagy: it takes guts to deliver. (3rd August 2022) - Raimundo, Nuno
Abstract : Refeeding after a period of starvation is known to suppress autophagy in the liver. Surprising new work by Seok et al (2022) shows that refeeding activates lipophagy in the intestine, which may help fats in our diet to be efficiently processed after a meal. Abstract : The activation of lipophagy in the intestine after feeding shows that different tissues can use autophagy in very different ways.